Análise da fluidodinâmica de calor em leito de jorro com alimentação contínua de sólidos pela base - Lima, Patrícia Moreira (Universidade Federal de São Carlos, 2004)
The objective of this work was to develop a theoretical and experimental study of fluid dynamics and heat transfer in a spouted bed with draft tube, which operates in continuous mode with particles feed through the bottom of the bed. This arrangement was chosen in order to maintain axial symmetry inside the bed. The chosen model was a steady-state model with axial variation, where balance equations describe the behavior of the solid and fluid phases both in the spout and annulus regions. A cylindrical-conical bed was used with draft tube and with a solids feed section attached to a gravitational system. The cylindrical column has 45 cm height and 20 cm diameter. The conical base has 15 cm height and internal angle of 600, and the air entrance has 5 cm diameter. The draft tubes have 5 cm diameter and two different heights of 18 and 28 cm. In the experiments glass spheres (dp=2.6 mm) were used for fluid dynamics and heat transfer study. The experimental conditions were: air flow rates of 2,1 and 2,5 m3/min; solids flow rates of 1100, 1500 and 2000 g/min; air temperatures of 80 and 90ºC; and bed heights of 25 and 35cm. The equations of the model were resolved in the program language Matlab by using numeric functions of high performance. The obtained profiles of the fluid dynamic and thermal model showed coherence in the qualitative aspects, because they agree physically with the expected for the spout. The analysis for quantitative comparison between the model and the experiment showed that the gas temperatures in the exit of the bed were predicted with smaller deviations than 3% and the solids temperatures with smaller deviations than 2%. Therefore, the results indicate that the investigated model can be applied in projects of spouted beds with similar characteristics and the bottom solids continuous feed by gravity maintained the axial symmetry of the bed.
Keywords: Industria química; Fluidodinâmica; Calor - transmissão; Leito de jorro; Operaçao contínua; ENGENHARIAS::ENGENHARIA QUIMICA